BENTUK PENYAJIAN TALEMPONG DUDUAKDALAM ACARA BAGARAK DI NAGARI AMPALU, KECAMATAN LAREH SAGO HALABAN, KABUPATEN LIMA PULUH KOTA - Nila Suryati Anggini; Marzam Marzam; Syahrel Syahrel (SENDRATASIK UNP, 2016)
This article aims to describe the form of presentation talempong duduak event in the village bagarak Ampalu, District Lareh Sago Halaban, Regency  Lima Puluh Kota. This type of research is qualitative descriptive approach. The data were collected by library research techniques, observation, interviews and documentationTalempong duduak Ampalu village named talempong malayu nan panjang by Art community consists of 6 pieces talempong tone, oguang and gondang .. As for the songs played that pararakan, gang loban timbang baju  Muaro paneh and more varied in its presentation such as rhythm, melody and poetry. Talempong duduak Ampalu village is a traditional music ensemble in which an exchange of position players, the addition and subtraction of players every exchange songs. Songs Muaro paneh presented strophic but at certain moments of melodic chant connect talempong. Songs pararakan and gang loban timbang baju  presented with interlocking technique with the pattern of the game each bar is the same and repetitive.